How do inner and outer settings affect implementation of a community-based innovation for older adults with a serious illness: a qualitative study - Grace Warner; Emily Kervin; Barb Pesut; Robin Urquhart; Wendy Duggleby; Taylor Hill (BMC, 2021)
Abstract Background Implementing community-based innovations for older adults with serious illness, who are appropriate for a palliative approach to care, requires developing partnerships between health and community. Nav-CARE is an evidence-based innovation wherein trained volunteer navigators advocate, facilitate community connections, coordinate access to resources, and promote active engagement of older adults within their communities. Acknowledging the importance of partnerships between organizations, the aim of our study was to use the Consolidated Framework for Implementation Research (CFIR) to explore organizational (Inner Setting) and community or health system level (Outer Setting) barriers and facilitators to Nav-CARE implementation. Methods Guided by CFIR, qualitative individual and group interviews were conducted to examine the implementation of Nav-CARE in a Canadian community. Participants were individuals who delivered or managed Nav-CARE research, and stakeholders who provided services in the community. The Framework Method was used to analyse the data. Particular attention was paid to the host organization's external network and community context. Results Implementation was affected by several inter-related CFIR domains, making it difficult to meaningfully separate key findings by only inner and outer settings. Thus, findings were organized into themes informed by CFIR, that cut across other domains and incorporated inductive findings: intraorganizational perceptions of Nav-CARE; public and healthcare professionals' perceptions of palliative care; interorganizational partnerships and relationships; community and national-level factors that should have facilitated Nav-CARE implementation; and suggested changes to Nav-CARE. Themes demonstrated barriers to implementing Nav-CARE, such as poor organizational readiness for implementation, and public and health provider perceptions palliative care was synonymous with fast-approaching death. Conclusions Implementation science frameworks and theories commonly focus on assessing implementation of innovations within facilities and changing behaviours of individuals within that organizational structure. Implementation frameworks need to be adapted to better assess Outer Setting factors that affect implementation of community-based programs. Although applying the CFIR helped uncover critical elements in the Inner and Outer Settings that affected implementation of Nav-CARE. Our study suggests that the CFIR could expand the Outer Setting to acknowledge and assess organizational structures and beliefs of individuals within organizations external to the host organization who impact successful implementation of community-based innovations.